The effect analysis of Zhang Jike`s return serve with backhand side-twisted at the 2/3 court right - 2012 London Olympic table tennis singles - Huang, W.; Zhang, H. (International Journal of Table Tennis Sciences, 2013)
With the methods of literature review and mathematic statistics, the paper analyzes the effect of Zhang Jike`s return serve with backhand side-twisted at the 2/3 court right, providing some references to the enrichment of receive methods. The study holds that there is more stability and more chances of direct score for Zhang Jike with backhand side-twisted than with forehand drive. However, the positioning defect after the side -twisted receiving may lead to the passive situation.